Antecedents of Customer E-loyalty With the Effect of Trustworthiness in Malaysia Context - Wong, Poh-Ming Winnie; Lo, May-Chiun; Ramayah, T. (David Publishing Company, 2014)
The rapid growth of online shopping has led to inspire customer e-loyalty among Malaysians, especially living in this digital environment. Commitment-trust theory is applied as the theoretical base to explain the factors influencing customer e-loyalty. The primary objective of this study is to investigate the direct impact of customer interface quality, service quality (SERVQUAL), website quality, technology acceptance factors, and technology trust on customer e-loyalty. This study also aims to examine the indirect effect of independence variables on customer e-loyalty through the effects of trustworthiness. SmartPLS 2.0 (M3) is applied as analytical tool to study the impact. A survey is conducted with 395 respondents who had online purchase experience. The findings indicated that customer interface quality, SERVQUAL, website quality, technology acceptance factors, and technology trust have positive impact on customer e-loyalty. Additionally, trustworthiness is used as mediator exclusive of SERVQUAL. Several implications of the findings, limitations of the study, and recommendations for future research are highlighted.